Regulation of air pollution from wood-burning stoves - Thomas Bue Bjørner; Jørgen Brandt; Lars Gårn Hansen; Martin Groth Hjelmsø; Marianne Nygaard Källstrøm (University of Copenhagen, Department of Food and Resource Economics (IFRO), 2016)
Air pollution is a major global challenge. Emissions from residential wood-burning stoves make a surprisingly large contribution to total air pollution related health costs. In Denmark, emissions from wood-burning stoves are calculated to cause almost 400 premature deaths each year within Denmark and additionally about 300 premature deaths in other parts of Europe. In this article, we present an integrated assessment of the net social benefit of different schemes for regulating wood-burning stoves including bans and taxes. The assessment uses high resolution air pollution emission inventory, and atmospheric dispersion and exposure models to estimate the health effects of imposing regulations on residential wood-burning. This is combined with an economic stove investment and use model to simulate reactions to regulations and evaluate compliance costs. We find that there are large net welfare gains from most types of regulation, but the largest gains result from imposing a differentiated tax or a general ban on older stoves. The results for Denmark suggest that there could be substantial welfare gains from regulating residential wood-burning stoves in other countries as well.
Keywords: I18; Q48; Q53; Q58; 330; wood-burning stoves; particle emission; cost-benefit; regulation; integrated assessment